Rusts on Ornamentals in Florida - Philip F. Harmon; Carrie L. Harmon; Aaron J. Palmateer; Stephen H. Brown (EDIS)
PP-256, a 6-page illustrated fact sheet by Philip F. Harmon, Carrie L. Harmon, Aaron J. Palmateer, and Stephen H. Brown, presents information on four representative rust diseases of ornamentals, including gladiolus rust, daylily rust, frangipani rust, and guava rust. Includes references. Published by the UF Department of Plant Pathology, May 2009.